Biomechanical relationships within the shoulder joint - Cornelius, W. (Technique, 1998)
The shoulder joint consists primarily of the glenoid fossa of the scapula and humeral head. Relationships between the humerus and scapula are particularly apparent in successful gymnastics performance. Although humerus movements are more obvious than scapula actions, the scapula plays an integral part in productive shoulder joint function. There would be little success during gymnastics performance without a scapula that fully accommodates movements of the humerus. A problem arises when there is inadequate cooperation between these bony segments at the shoulder joint. Gymnastics performance typically is associated with a wide range of humerus movements, from such action patterns as hyper-flexion to hyper-extension and from hyper-abduction to adduction.